INFLUENCE OF E-COMMERCE ATTRIBUTES ON CUSTOMER SATISFACTION AND LOYALTY - Kostić, Sara (Ekonomija - teorija i praksa, 2022)
The Internet has provided retailers with a whole new way of conducting business, reducing fixed costs such as renting space, but at the same time a way of increasing the need to develop and invest in digital marketing tools, sales promotions and after-sales services. A large number of virtual stores where customers can shop without leaving their home or workplace have been opened. Marketing research was conducted with the aim of analyzing the impact of e-commerce attributes on customer satisfaction and loyalty in the Republic of Serbia. Seven hypotheses have been tested in this paper. Observing the importance of all constructs, it has been found that the attributes of e-commerce are extremely important and that almost all of them affect satisfaction. The impact of website security on customer satisfaction has proven to be less relevant, and the quality of information does not directly affect customer loyalty. This research has shown that the development of e-commerce in the Republic of Serbia is growing, and that customers are increasingly preferring this type of shopping. The golden thread in this paper is its ability to collectively measure the factors that affect the satisfaction and loyalty of online consumers. At the very end of the paper, economic implications are given, as well as recommendations for further research.